The book of wonders - Richards, Jasmine (Harper, 2012)
In a tale loosely based on the Arabian nights, thirteen-year-old Zardi and her best friend, Ridhan, join forces with Captain Sinbad to defeat an evil sultan and restore magic to the world of Arribitha.